Small children but big numbers: Estimating the economic benefits of addressing undernutrition - Alderman, Harold (2018)
Harold Alderman IFPRI-FAO conference, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand